OPTIMIZATION OF CARGO ROUTES BASED ON THE MODIFIED ANT ALGORITHM - Lesnikova, Irina Y.; Khalipova, Natalia V.; Sazonets, Olga M.; Rudyanova, Tatyana M. (Systems and Technologies, 2022)
Summary. The article is devoted to solving complex problems of optimization of freight transportation, namely search and determination of the most suitable solution for optimizing (finding a minimum or maximum) the target function (price, accuracy, time, distance, etc.) from a discrete set of possible solutions. The article substantiates the direction of modification of the ant algorithm, an algorithm for routing the implementation of the transport process is formed on the basis of the study of the state and determination of the theoretical throughput of individual sites on the projected routes. As well as an analysis of the effectiveness of classical and modified algorithms on the example of designing optimal routes from the point of departure to the destination and to find the maximum freight route. Among the modern methods for solving the problem of a salesman, an ant algorithm is chosen, since its physical basis – the behavior of ants when searching for food – is the closest to formulating this problem, which determines the optimal route for transportation and its profitability for the company. A mathematical model was constructed, an algorithm was proposed and a flowchart was developed to determine the optimal transportation route based on a modified ant algorithm. A program was developed in the Delphi environment to determine the optimal route by the minimum distance criterion based on the proposed algorithm of the salesman problem. The task of determining the shortest route, which includes regional centers of Ukraine, is connected and a graph of this route is constructed. The optimal route was developed: Kyiv - Zhytomyr - Lutsk - Chernivtsi - Uzhgorod - Lviv - Ivano-Frankivsk - Khmelnytsky - Cherkasy - Zaporizhzhia - Kharkiv - Chernihiv - Nikolaev - Kirovograd - Dnipro - Poltava - Sumy - Vinnytsia - Ternopil - Rivne - Kherson - Odessa - Kyiv, with a total distance of 7,930 km and a freight of 190,710 UAH. A program has been developed in the Delphi environment to determine the optimal route according to the maximum freight criterion of the carrier based on the proposed algorithm of the salesman problem. This task is connected for a network of 22 cities – regional centers of Ukraine, and a graph of the received route was constructed. The optimal route was developed: Kyiv – Mykolaiv – Chernivtsi – Zhytomyr – Khmelnytskyi – Dnipro – Lutsk – Kirovohrad – Rivne – Kherson – Sumy – Ternopil – Chernihiv – Vinnytsia – Poltava – Odesa – Lviv – Kharkiv – Uzhgorod – Zaporizhzhia – Ivano-Frankivsk – Cherkasy – Kyiv, with a total freight for the carrier of UAH 357,800 and a distance of UAH 16,170 km. Justification of optimal routes is quite an important task for the effective operation of logistics companies, since freight transportation is extremely important for the economy of the country and the company and is relevant in the present. According to the results of calculations, technical solutions have been developed to improve the efficiency of the logistics company on the basis of a modified ant algorithm.